How EFL teacher Modelling Politeness: Pragmatic Analysis of Classroom Interaction - Nuril Habibatus Sa'idah; Toyyibah Toyyibah (Alsuna: Journal of Arabic and English Language, 2022)
Purpose- This study aims to find the types of politeness strategies used by English teachers during the learning process. Design/methodology/approach- This study uses a qualitative research method with ethnographic communication design to find politeness strategies in speech used by English teachers at SMA Negeri 1 Prambon. Research data were taken through observation and interviews. Researchers used a coding scheme to analyze the data that has been obtained. Findings/results – It was found 134 teacher utterances, classified according to politeness strategies that were applied during the English learning process. Of the 134 teacher utterances, there are 35 utterances categorized as positive politeness strategies, 8 utterances as negative politeness strategies, 69 as bald on-record politeness strategies, and 22 utterances as off-record politeness strategies. In other words, the bald on-record strategy is the dominant politeness strategy used by English teachers during the learning process. Thus, the politeness strategies used by teachers are influenced by certain conditions and situations in the classroom. Originality/value - Politeness strategy is a very crucial thing which needs to be considered in its use based on the appropriate conditions and situations, especially by the teacher as an example or role model for his students is not the case in the delivery of subject matter but also attitude or speech. Paper type – Research paper Keywords: Teacher talk, pragmatic, politeness strategies